2022
DOI: 10.5455/medscience.2022.08.176
|View full text |Cite
|
Sign up to set email alerts
|

Dissoanalysis as a Modern Psychotraumatology Theory: Denial Trauma and Mass Dissociation versus Dissociative Revolution and Psychocommunal Therapy

Abstract: The "theory of dissoanalysis", structured on an axis that has the closest interactional dynamic with each individual and social element of the "multiple consciousness system" and "multiple memory phenomenon" conjugated with traumatic experiences, has its scientific roots in modern psychotraumatology studies conducted by Öztürk, a trauma therapist and a psychohistorian. Dissoanalysis makes significant scientific contributions to the development of both effective psychotherapy methods and innovative psychotrauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(104 citation statements)
references
References 18 publications
0
104
0
Order By: Relevance
“…"Resilience", which consists of personal, relational or cultural components, should be one of the main elements to be worked on in the traumatized individual, unnecessary attempts to intervene should be avoided and the person should be supported to be in a solution-oriented position that aims to continue his/her current life by overcoming difficulties rather than being a helpless victim in the process. An ideal crisis intervention approach for traumatized individuals includes allowing the expression of emotions in the acute period, breaking the cycle of negative thoughts, and revealing appropriate expressions for the desired reactions under the guidance of the psychotherapist [5,17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…"Resilience", which consists of personal, relational or cultural components, should be one of the main elements to be worked on in the traumatized individual, unnecessary attempts to intervene should be avoided and the person should be supported to be in a solution-oriented position that aims to continue his/her current life by overcoming difficulties rather than being a helpless victim in the process. An ideal crisis intervention approach for traumatized individuals includes allowing the expression of emotions in the acute period, breaking the cycle of negative thoughts, and revealing appropriate expressions for the desired reactions under the guidance of the psychotherapist [5,17].…”
Section: Discussionmentioning
confidence: 99%
“…Social traumas can be neutralized through a "psychosocial therapy" called the "dissoanalysis method" in the axis of dissoanalytic psychohistory and modern psychotraumatology theories. Without the dissoanalysis of traumatized individuals and societies, no nation can escape from its violence-focused borderline components and achieve an integrative life organization [5][6][7].…”
Section: The Concept Of Social Traumamentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have explicitly indicated a correlation between dissociative experiences and childhood trauma and it can be stated, with certainty, that childhood trauma is one of the most basic etiological elements of somatoform dissociation and psychoform dissociation [13,15,[35][36][37]. During or after traumatic experiences, these trauma victims show somatization reactions in the body (such as fibromyalgia) or psychoform dissociation reactions that occur mentally [15,16].…”
Section: Discussionmentioning
confidence: 99%